Separation of high-value extracts from Silybum marianum seeds: Influence of extraction technique and storage on composition and bioactivity. (15th April 2022) - Lukic, Ivana; Milovanovic, Stoja; Pantic, Milica; Srbljak, Ivana; Djuric, Ana; Tadic, Vanja; Tyśkiewicz, Katarzyna
Abstract: Extracts from Silybum marianum seeds have high industrial potential due to their application as phytopharmaceuticals and food. In order to optimize its production, conventional extraction (in Soxhlet apparatus using solvents ethanol and n -hexane) and supercritical fluid extraction (using CO2 at the pressure of 30 MPa and temperature of 40 °C with and without co-solvent ethanol, from oil-rich and defatted seeds) were compared. In addition, the effect of plant cultivation (years 2011 and 2019) and the effect of seeds and extract storage on the yield and quality of extracts were assessed. It was shown that unsaturated fatty acids (linoleic and oleic acids being most dominant) constituted 64–87% of obtained extracts. Content of α-tocopherol varied from 0.01 to 13 g/100 g, while total phenolic content was in the range from 13.2 to 104.2 gGAE /100 gextract . In vitro cytotoxic activity analysis confirmed that extracts obtained from defatted seeds showed activity against cancer cells. This study pointed out the important role of the cultivation year, selection of extraction technique and solvent, as well as storage on the extraction yield, chemical profile, and cytotoxic activity of extracts. Highlights: Year of plant cultivation and storage determined extract amount and composition. Unsaturated fatty acids constituted 64–87% of obtained extracts. Content of α-tocopherol in extracts varied from 0.01 to 13 g/100 g. Total phenolic content was in the range from 13.2 to 104.2 gGAE /100 gextract . Supercritical extracts from S. marianum defatted seeds exhibited cytotoxic activity.